2017
DOI: 10.1002/ppap.201700122
|View full text |Cite
|
Sign up to set email alerts
|

Surface modification of polysulfone hollow fiber membrane for extracorporeal membrane oxygenator using low‐temperature plasma treatment

Abstract: The surface of polysulfone (PSF) hollow fiber membranes (HFMs) was modified to improve the hemocompatibility of pristine PSF membrane for use in extracorporeal membrane oxygenators using low‐temperature plasma treatment. Acrylic acid (AA) with heparin, 2‐methacryloyloxyethyl phosphorylcholine (MPC), and collagen were grafted on the PSF surface to prepare PSF‐AA‐Hep, PSF‐MPC, and PSF‐Col membranes, respectively. The surface‐modified membranes were analyzed by Fourier transform infrared spectroscopy (FTIR), UV‐v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The low-temperature plasma treatment (LTPT) was extensively used in membrane surface modification. Zheng et al [ 77 ] reported a successful surface modification of the PSF membrane via LTPT and grafting acrylic acid (AA) and PEG, 2-methacryloyloxyethyl phosphorylcholine (MPC), heparin and collagen ( Figure 9 ). Zhang et al [ 78 ] described a surface modification of the PSF via ammonia–oxygen (NH 3 –O 2 ) plasma treatment and found that the hydrophilicity of membrane was improved in comparison with pristine PSF membrane.…”
Section: Polysulfone Functionalized Membranes For Hemodialysismentioning
confidence: 99%
“…The low-temperature plasma treatment (LTPT) was extensively used in membrane surface modification. Zheng et al [ 77 ] reported a successful surface modification of the PSF membrane via LTPT and grafting acrylic acid (AA) and PEG, 2-methacryloyloxyethyl phosphorylcholine (MPC), heparin and collagen ( Figure 9 ). Zhang et al [ 78 ] described a surface modification of the PSF via ammonia–oxygen (NH 3 –O 2 ) plasma treatment and found that the hydrophilicity of membrane was improved in comparison with pristine PSF membrane.…”
Section: Polysulfone Functionalized Membranes For Hemodialysismentioning
confidence: 99%
“…Zheng, et al [81] compared different materials, i.e. acrylic acid with heparin (AA-Hep), 2-methacryloyloxyethyl phosphorylcholine (MPC), and collagen, to study their biocompatibility.…”
Section: Surface Modification Of Membrane Oxygenatormentioning
confidence: 99%
“…Membrane oxygenators are usually fabricated using polymeric materials, such as polysulfone [15], polyurethane [16], polypropylene [17], polyimide [18], and silicon [19][20][21][22]. Among these polymers, non-porous silicon-based hollow fiber is used in commercial ECMO systems due to its ability to avoid plasma leakage during the long time of extracorporeal circulation.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, they lead to increased mass-transfer coefficients of the required component from one phase to another and, consequently, to compact separation modules [3]. Gas-liquid membrane contactors are already widely used for various applications, including blood oxygenation [4,5], the removal of acid gases (CO 2 , H 2 S, SO 2 ) from gaseous media [6,7], the removal of dissolved gases from liquids [8,9], and the separation of saturated and unsaturated hydrocarbons [10].…”
Section: Introductionmentioning
confidence: 99%